Strategy Formulation and its Business Model in Griya Buku Net - Isthika, Florentia Anindita Apsari; Wandebori, Harimukti (Journal of Business and Management, 2013)
Griya Buku Net (GBN) was an online based bookstore that aims to provide all kind of books with affordable price. In middle of 2012, Griya Buku Net was still a startup family business but in effort of moving to running business. Griya Buku Net sells books in various genres, both new and old books, and offering special request books service that becomes the specialty of Griya Buku Net. Based in Bandung, Griya Buku Net has sent thousands of books to all corners of Indonesia. The value proposition that Griya Buku net offer makes it unique compared to others, but the business model itself was still need an improvement. For the research, both primary and secondary data been used to gather the information and findings through observation, interviews, and secondary data collection. The descriptive research heavily relies on in-depth interview with the owner and the financial data of Griya Buku net for EVA valuation. The primary tools used were Basic Strategic Management model and Basic Nine Blocks Business Model as the proposed strategy. For the findings, it was concluded that the internal and external factors of Griya Buku Net affect the business in term of defining the current’s corporate position. From the EFAS and IFAS Table and SFAS Matrix, the current corporate directional strategy for Griya Buku Net was Diversification Strategy. For the business activity, it was defined through value chain analysis. As the activity linkage was based on financial planning, consequently financial target of 5 years were set to the company’s objective through EVA Valuation. Using an annual fiscal period of July 2012 to June 2013 sales and transaction data, the corresponding calculation on EVA Table has shown that the economic value added of Griya Buku Net still stands at a low 1.3 million rupiah. But if things happen as the annual target, in the end of 2018, the EVA will stand at high 2.6 billion rupiah. Next, the business strategy was defined through Porter’s Generic Competitive Strategy as Differentiation Focus. For functional strategy, it was determined through the TOWS Matrix Strategy Analysis, and was expanded to the Basic Nine Blocks Business Model. The TOWS Matrix and Business Model were derived from company’s vision, mission, 5-years annual target, and previously formulated corporate and business activity. In result, the findings that there’s strong potential in niche market may change the direction of the business. According to its strength and external factors both opportunities and threats, rare books can become an option for the sustainability and uniqueness of the business. The rare books also become the main value proposition in the new business model. The business model as well, was formulated to accommodate the company strategies and can be used as the basic model for running the business. The functional strategies and strategic planning for each aspect of business resources and activity was conveyed through performance management, and will help the business for its sustainability to achieve the overall company objectives.  Keywords: Strategic Management, EVA Valuation, Business Model, Bookstore------------------------DISCLAMER: This paper is created by undergraduate students of School of Business and Management ITB in partial fulfillment of the requirement of the degree Bachelor of Management. Journal of Business and Management is not responsible for the content, opinions, or any other materials expressed here.